“GERAHAM MODEL” As a Strategy to Improve Mother’s Behaviour Maintance in Brushing Teeth - Rasipin Rasipin; Masrifan Djamil; Bedjo Santoso (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2022)
The results of Riskesdas 2018, showed 93% of children aged 5-6 years had dental caries with an average DMF-T of 8.3; as many as 57.6% experienced dental and oral health problems, and only 10.2% received services from medical personnel. The number of dental health problems in Central Java is below the national threshold of 57.6%. The proportion of dental health problems in Indonesia is still far from the expectation of achieving the long-term target of the Ministry of Health in 2030. Indonesia is caries-free. The aims of this study was to produce a